Sjögren's Syndrome: A Rare Clinical Entity in Children - Laila Hamri (Indonesian Rheumatology Associantion, 2023)
Background. Sjögren's syndrome (SS) is a rare autoimmune disease inchildren, with only a few hundred reported cases. Its clinical presentation isatypical. We report the case of a 14-year-old boy diagnosed with recurrentparotitis. Case Presentation. Our patient, a 14-year-old male, presentedwith a one-year history of recurrent bilateral parotid swellings. Clinicalexamination revealed an objective oculo-buccal dryness. Ultrasound imagingshowed hypoechoic hypertrophy of the parotid glands. Anti-SSA/SSBantibodies were strongly positive. Histological study of the accessory salivaryglands revealed lymphocytic sialadenitis with a focus score of 3. Thediagnosis of SS was confirmed according to the ACR/EULAR 2016 criteria.The combination of treatment with hydroxychloroquine and corticosteroidsresulted in the resolution of clinical signs and biological inflammatorymarkers. Conclusion. Given the rarity of SS in children, several diagnosticand therapeutic difficulties arise, in the absence of classification criteriaadapted to the juvenile form of the disease, and the absence of therapeuticrecommendations consolidated by clinical trials in children.